Stream stability and scour at highway bridges : water resources engineering : compendium of stream stability and scour papers presented at conferences sponsored by the Water Resources Engineering (Hydraulics) Division of the American Society of Civil Engineers, conferences were held at Nashville, Tennessee, July 29-August 2, 1991 ... Memphis, Tennessee, August 3-5, 1998 - Richardson, E. V. (Everett V.), 1924-; Lagasse, Peter F. (Peter Frederick), 1937- (American Society of Civil Engineers, 1999)
"This book is a compendium of 75 papers and 321 abstracts presented at conferences sponsored by the Water Resources Engineering (Hydraulics) Division of the American Society of Civil Engineers from 1991 through 1998. It contains many new and expanded versions of the original papers, and is designed to assist the practitioner with the concepts in evaluating stream instability and scour at bridges."--BOOK JACKET.